2007
DOI: 10.1007/s00114-007-0315-2
|View full text |Cite
|
Sign up to set email alerts
|

Clockwork blue: on the evolution of non-image-forming retinal photoreceptors in marine and terrestrial vertebrates

Abstract: This paper presents a hypothesis that could explain why blue light appears to dominate non-image-forming (NIF) ocular photoreception in marine as well as terrestrial vertebrates. Indeed, there is more and more evidence suggesting that 'novel' retinal photoreceptors, which are sensitive to blue light and were only discovered in the 1990s, could be a feature shared by all vertebrates. In our view, blue light photoreception evolved and persisted as NIF photoreception because it has been useful in the colonisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…We and other groups also demonstrated that the eye of Limax is more responsive to short-wavelength blue light, especially when the eye is light adapted (Suzuki et al, 1979;Matsuo et al, 2017Matsuo et al, , 2019. The preferential use of short-wavelength light is thought to be a widely conserved phenomenon in the animal kingdom (Gehring and Rosbash, 2003;Erren et al, 2008), and the slugs also appear to have inherited this trait.…”
Section: ) Andsupporting
confidence: 54%
“…We and other groups also demonstrated that the eye of Limax is more responsive to short-wavelength blue light, especially when the eye is light adapted (Suzuki et al, 1979;Matsuo et al, 2017Matsuo et al, , 2019. The preferential use of short-wavelength light is thought to be a widely conserved phenomenon in the animal kingdom (Gehring and Rosbash, 2003;Erren et al, 2008), and the slugs also appear to have inherited this trait.…”
Section: ) Andsupporting
confidence: 54%
“…Many photoreceptors involved in non-image-forming tasks appear to peak close to 480 nm, with a spread ranging from 460 to 530 nm. Melanopsin seems to be a common feature of all vertebrates (Table 1) that mediates non-visual retinal photoreception, which is dominated by blue light both in aquatic and terrestrial vertebrates [51]. Photoreceptive pigments generally evolved to mediate specific photoreceptive tasks in different photic environments [26].…”
Section: Evolutionary Aspects Of Diverse Photoreceptive Organsmentioning
confidence: 99%
“…More recently, nocturnal production levels of melatonin have been shown to be inversely correlated with irradiances of narrowband blue LED light (peak l ¼ 469 nm; half peak bandwidth ¼ 26 nm) and the suppression impact of this narrow spectrum was more severe than that of 4000k white florescent light at twice the energy of the former [56,61]. Interestingly, blue-shifted photosensitivity of the retinal non-visual photoreceptors is postulated to be a conserved adapted feature of all vertebrates, which initially was adapted to the local blue-rich spectral composition of oceanic environments and selected later to be a unique ocular feature of all terrestrial vertebrates [62]. ALAN pollution has become a major problem for both environment stability and human health.…”
Section: Melatonin Suppressionmentioning
confidence: 99%